Differential proteome analysis of pea roots at the early stages of symbiosis with nodule bacteria - I. V. Leppyanen; A. N. Kirienko; A. A. Lobov; E. A. Dolgikh (Вавиловский журнал генетики и селекции)
In this paper, we have analyzed changes in the proteomic spectrum of pea Pisum sativum L. roots during inoculation with rhizobial bacteria with the aim of revealing new regulators of symbiosis development. To study the changes in the proteome spectrum of pea roots, a differential twodimensional (2-D) electrophoresis was performed using fluorescent labels Cy2 and Cy5. The images obtained made it possible to identify differences between the control variant (uninoculated roots) and the root variant after inoculation with Rhizobium leguminosarum bv. viciae RCAM 1026 (24 hours after treatment). 20 proteins were revealed and identified, the synthesis of which was enhanced during the inoculation of pea roots by nodule bacteria. To identify the proteins, a mass spectrometric analysis of tryptic peptides was performed on a quadrupole-time-of-flight mass spectrometer combined with a high-performance liquid chromatograph. Among such proteins, the beta-subunit of the G protein and the disulfide isomerase/phospholipase C were first found, whose function can be related to the signal regulation of symbiosis. This indicates that G-proteins and phospholipases can play a key role in the development of early stages of symbiosis in peas. Further experiments are expected to show whether the beta-subunit of the G protein interacts with the receptors to Nod factors, and how this affects the further signaling. Other proteins that might be interesting were annexin D8 and D1, protein kinase interacting with calcinerin B, actin-binding protein profilin, GTP-binding protein Ran1. They may be involved in the regulation of reactions with calcium, the reorganization of the actin cytoskeleton and other important processes in plants. The study of the role of such regulatory proteins will later become the basis for understanding the complex system of signal regulation, which is activated in pea plants by interaction with nodule bacteria.